(untitled) (Proceedings of International Educators Conference, 2023)
This article analyzed the factors that motivated the beginning of relations between the Safavid state and Europe, the processes of departure of these relations, the achievements of the royal government in diplomatic relations, as well as its consequences and what factors led to the failure of embassy missions.